Program for climate-smart livestock systems. Country stocktake: Uganda - Thornton, Philip K.; Enahoro, Dolapo K.; Njiru, Nelly M.; Wijk, Mark T. van; Ashley, Laurie; Cramer, Laura K.; Ericksen, Polly J.; Graham, Michael (International Livestock Research Institute, 2019)
This is one of a series of documents that summarises information relating to the livestock sector in the three Program for Climate-Smart Livestock Systems (PCSL) project countries (Ethiopia, Kenya and Uganda). Prevailing livestock systems and their baseline performance in Uganda are summarised first, followed by a summary of what is known about the impacts of climate change on livestock production and livestock systems. Section 4 briefly summarises some recent research on adaptation and mitigation options for livestock systems in Uganda. Section 5 considers some of the work that has been done to date on projections for the livestock sector to the middle of the century. Section 6 considers the national livestock and climate change policy environment. The paper concludes with a consideration of system intervention points and major gaps in knowledge, to help guide project activities in Uganda.